A Scrutiny of the Software Requirement Engineering Process. (2016) - Geogy, Manju; Dharani, Andhe
Abstract: Current complexities and high client expectations of an application, the software development is more being an art with a mix of technical experts and managerial techniques. Due to globalization, software and technology are the part of any automated entity. Each and every organization expects a good and reliable software technology working with it. In any domain, building an application is a challenging task due to the lack of requirements gathering or the developer not understanding the actual needs of the client. There are multiple tools to collect the requirements from the clients. The major faults are occurring in requirement analysis phase. Which is considered a sensitive task, any mistakes or wrong perception may lead to major catastrophic for the end product. By considering all facts about requirement engineering the study here gives the basics and some of the key challenges in the requirement analysis phase of software process.